Effect of rainfall interval on loss rates - Heng, Pei Kiat. (2010)
Computer models based on kinematic wave theory can be developed to simulate the rainfall-runoff process on a catchment. In this study, computer models have been developed for a natural catchment (Upper Bukit Timah Drainage Basin) and two artificial catchments (Concrete and Asphalt Planes) to evaluate their respective optimum loss rates for the two loss models when catchments are subjected to natural rainfall. The loss models used are the upperbound loss model and the proportional loss model.